Acute Pancreatitis and Splenic Vein Thrombosis due to Hypertriglyceridemia. (23rd February 2015) - Gündüz, Ercan; Dursun, Recep; İçer, Mustafa; Zengin, Yılmaz; Güloğlu, Cahfer
Abstract : Acute pancreatitis (AP) is a condition characterised by the activation of the normally inactive digestive enzymes due to an etiological factor and digestion of the pancreatic tissues, resulting in extensive inflammation and leading to local, regional, and systemic complications in the organism. It may vary from the mild edematous to the hemorrhagic and severely necrotising form. The most common causes are biliary stones and alcohol abuse. In this case study, we would like to present a patient with AP due to hypertriglyceridemia (HPTG), which is a rare cause of pancreatitis, and splenic vein thrombosis, which is a rare complication of pancreatitis.